2016
DOI: 10.1002/2015gb005237
|View full text |Cite
|
Sign up to set email alerts
|

The Greenland Ice Sheet as a hot spot of phosphorus weathering and export in the Arctic

Abstract: The contribution of ice sheets to the global biogeochemical cycle of phosphorus is largely unknown, due to the lack of field data. Here we present the first comprehensive study of phosphorus export from two Greenland Ice Sheet glaciers. Our results indicate that the ice sheet is a hot spot of phosphorus export in the Arctic. Soluble reactive phosphorus (SRP) concentrations, up to 0.35 μM, are similar to those observed in Arctic rivers. Yields of SRP are among the highest in the literature, with denudation rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
189
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 146 publications
(198 citation statements)
references
References 110 publications
9
189
0
Order By: Relevance
“…4d). In effect, NO 3 -became limiting before the exhaustion of PO 4 3-, indicating the existence of previously mentioned P-excess in the system (YamamotoKawai et al, 2006;Hawkings et al, 2016). One of the most plausible origins of this PO 4 3-excess is the glaciers from Greenland.…”
Section: Pml and Haloclinementioning
confidence: 78%
See 1 more Smart Citation
“…4d). In effect, NO 3 -became limiting before the exhaustion of PO 4 3-, indicating the existence of previously mentioned P-excess in the system (YamamotoKawai et al, 2006;Hawkings et al, 2016). One of the most plausible origins of this PO 4 3-excess is the glaciers from Greenland.…”
Section: Pml and Haloclinementioning
confidence: 78%
“…The physical erosion of bedrock exposes ground apatite to biogeochemical weathering ultimately liberating PO 4 3-to the Arctic Ocean. Hawkings et al (2016) suggested that the Greenland Ice Sheets are the region of most efficient P weathering and export of PO 4 3-to surrounding regions, and that the export of dissolved phosphorous could equal that of the largest rivers in the world, like the Mississippi and the Amazon. In this study, the N/P ratio was strongly modified in the surface waters.…”
Section: Pml and Haloclinementioning
confidence: 99%
“…An interesting consequence of the basal melt inputs may be the associated release of nutrients to the ocean. Recent work from the Greenland Ice Sheet indicates dissolved phosphorus yields are at least equal to those associated with the Mississippi or Amazon rivers (32). In this regard, nutrients from direct subglacial weathering should be considered in the future as a potential source to fuel productivity in the North Atlantic during HS1.…”
mentioning
confidence: 99%
“…In recent years, there has been an increasing effort to quantify the magnitudes of chemical transport from the GrIS to adjacent seas, with special emphasis on nutrient export (e.g., Hawkings et al 2014Hawkings et al , 2015Hawkings et al , 2016Hawkings et al , 2017Wadham et al 2016). These estimates are almost all based on an upscaling from the Watson River catchment, or the subcatchment Leverett Glacier, to the entire GrIS.…”
Section: Resultsmentioning
confidence: 99%